The Increasing Risk of Dementia in Psoriasis: A Systematic Review and Meta-Analysis - Chayada Chaiyabutr (2022)
Objective: To systemically summarize and meta-analyze the risk of dementia in psoriasis patients. Methods: A systematic review was performed in two databases (EMBASE and MEDLINE). The eligible studies had to be a cohort study or a cross-sectional study that compared either the prevalence or incidence of dementia in psoriatic patients, versus comparators without psoriasis. Results: Of 791 retrieved articles, seven studies met the inclusion criteria and were included into this systematic review and meta-analysis. The risk of incident and prevalent dementia were significantly higher in psoriatic patients, with a pooled risk ratio of 1.16 (95% CI: 1.02-1.33; I296%) and 1.36 (95% CI: 1.07-1.72; I210%), respectively. Conclusion: This study revealed a slight increase in both the incidence and prevalence of dementia in psoriasis patients. However, dermatologists should carefully observe and periodically screen psoriasis patients for this comorbidity, especially among those who have symptoms and signs of cognitive impairment.